Not-for-profit budgeting for nonprofit organizations - McMillan, Edward J., 1949- (Wiley, 2010)
Take control of your organization's short- and long-term financial plan. Now fully revised, Not-for-Profit Budgeting and Financial Management, Second Edition, offers a financial planning system that is not only easy to use and monitor, but also ensures true fiscal accountability in the complex not-for-profit arena.: Adds three entirely new chapters on Footnoting the Statement of Activity, Presenting Cash Prepared and Accrual Statements on the same page, and The Importance of the Executive Summary; Fully updated with the latest financial advice to benefit your nonprofit; Explains how to separa.